PENGARUH IMPLEMENTASI SISTEM AKUNTANSI, PENGELOLAAN KEUANGAN DAERAH DAN PENGAWASAN INTERNAL TERHADAP KINERJA KEUANGAN PEMERINTAH KABUPATEN ACEH UTARA - STIE Lhokseumawe (Sekolah Tinggi Ilmu Ekonomi Lhokseumawe, 2019)
This study aims to examine the effect of accounting system implementation, regional financial management and internal supervision to government financial performance at SKPD of North Aceh Regency. This study uses primary data obtained by distributing questionnaires to 60 employees who serve as research samples. The data were analyzed using a multiple linear regression. The results of the study show that partially; the implementation of the accounting system and internal supervision has a significant effect to the government's financial performance at SKPD of North Aceh Regency. Regional financial management has effect not significant to government financial performance at SKPD of North Aceh Regency. The simultant, accounting system implementation, regional financial management and internal supervision has a significant effect to the government's financial performance at SKPD of North Aceh Regency, which is influenced about 59.8% and 40.2% influenced by other variables outside of this research.